Reflexivity: The New Reflective Practice - Cousin, Glynis (International Journal of Practice-based Learning in Health and Social Care, 2016)
This brief paper seeks to expose contemporary thinking behind the notion of researcher reflexivity in order to draw out its usefulness for practice-based learning research and for a renewed perspective on reflective practice. Discussion includes social constructionist perspectives, questions of positionality, experiential affinity, the place of scholarship, language and the provenance of our explanatory frameworks. I conclude with a series of questions that can support a reflexive approach to practice-based learning and related research.